Conversion and compulsion : North/South bargaining on trade-related aspects of intellectual property rights (TRIP's) during the Uruguay Round of GATT negotiations - Vorster, Shaun (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1998.